Kesiapan Masyarakat Semarang dalam Pemanfaatan Potensi Energi Surya sebagai Sumber Energi Alternatif Berkelanjutan - Amalia; Zaenal Arifin; Aries Jehan Tamamy (Universitas Katolik Musi Charitas, 2018)
Electricity needs in Indonesia increase along with the growth of population, industry, and infrastructure development, which influences the availability of electricity in future generations. Semarang City is one of the big cities in Indonesia that requires electrical energy to support community operations and development. This study aims to explain the solar energy potential in the Semarang city, and to identify Semarang community readiness in the utilization of solar energy sources. Energy potential data was collected using direct observation, while data on community preparedness were obtained by distributing questionnaires. This research was analyzed descriptively qualitative. The results of the study explain that the potential of solar power plants is 5.4 KWH. In addition, the overall level of readiness of the city of Semarang is classified as high level of readiness (72.50%), with values of awareness of 82.5%(high) and knowledge of 67.25% (moderate).